MINAT SISWA SMK N KOTA PADANG KELAS XII JURUSAN TEKNIK BANGUNAN UNTUK MELANJUTKAN PERKULIAHAN DI PRODI PENDIDIKAN TEKNIK BANGUNAN FT-UNP - Arnold .; Iskandar G. Rani (CIVED, 2019)
Abstract – An Interest of vocational students to continue lecture in the Building Engineering Education Study Program is still relative low. It is seen from the number of students who came from SMK N in Padang City who is in college studying at the FT-UNP Building Engineering Education Study Program from 2015-2018, only 22 students. Therefore it is necessary to know about the interest of students of SMK N 1 Padang, SMK N 5 Padang and SMK N 1 West Sumatra Department of Building Engineering in continue lecture if reviewed from the type of information received by students. This research is descriptive research. The data analysis technique uses the calculation of degree of achievement (percentage). The degree of achievement calculated is the percentage of the type of information received by students such as educational information, employment information, and social information. The percentage results are then matched to a scale of 5 according to Riduwan to find out students' interest in continue lecture in the FT-UNP Building Engineering Education Study Program in terms of the type of information received by students. Research result: Interest of students of SMK N Kota Padang class XII of the Department of Building Engineering to continue lecture in the Building Engineering Education Study Program FT-UNP on education information 77.81% are in the quite interested category, work information 74.01% are in the quite interested category, and social information 72.33% are in the quite interested category. Keywords: Interest, lecture, Information.